Phenotypic and molecular analysis of Mexican Metarhizium anisopliae strains - Hortensia Navarro-Barranco; Carolina Brunner-Mendoza; María del Rocío Reyes-Montes; Esperanza Duarte-Escalante; Conchita Toriello (Revista Mexicana de Biodiversidad)
Metarhizium anisopliae is an anamorphic fungus widely studied due to its use as a biological control agent. In Mexico, it is mainly used as an integrated management strategy to control populations of spittlebugs (Hemiptera: Cercopidae) that affect sugarcane fields and cattle pastures. In this study, 13 strains isolated from Aeneolamia spp. (Hemiptera: Cercopidae) from the main areas of sugarcane production of Mexico and 11 reference strains of Metarhizium from different insect hosts and geographic origins were evaluated based on their conidial dimensions, thermotolerance at 15, 25, 30, and 35 ºC, random amplification of polymorphic DNA (RAPD) patterns using a combined analysis with 14 different oligonucleotides and diversity estimators, and a phylogenetic analysis with the ribosomal RNA internal transcribed spacer (ITS) region. All strains used in this study showed typical morphological characteristics corresponding to M. anisopliae and were able to grow at 25 and 30 ºC with restricted growth at low (15 ºC) and high temperatures (35 ºC). Polymorphism analysis clustered all strains from Aeneolamia sp. in one welldefined group with low variability among them. Phylogenetic relationships based on nuclear ribosomal ITS region sequences recovered a subclade within M. anisopliae formed by 10 of the Mexican strains.